Cultivated Tomato (Solanum lycopersicum L.) Suffered a Severe Cytoplasmic Bottleneck during Domestication: Implications from Chloroplast Genomes - Rachele Tamburino; Lorenza Sannino; Donata Cafasso; Concita Cantarella; Luigi Orrù; Teodoro Cardi; Salvatore Cozzolino; Nunzio D’Agostino; Nunzia Scotti (Plants, 2020)
In various crops, genetic bottlenecks occurring through domestication can limit crop resilience to biotic and abiotic stresses. In the present study, we investigated nucleotide diversity in tomato chloroplast genome through sequencing seven plastomes of cultivated accessions from the Campania region (Southern Italy) and two wild species among the closest (Solanum pimpinellifolium) and most distantly related (S. neorickii) species to cultivated tomatoes. Comparative analyses among the chloroplast genomes sequenced in this work and those available in GenBank allowed evaluating the variability of plastomes and defining phylogenetic relationships. A dramatic reduction in genetic diversity was detected in cultivated tomatoes, nonetheless, a few de novo mutations, which still differentiated the cultivated tomatoes from the closest wild relative S. pimpinellifolium, were detected and are potentially utilizable as diagnostic markers. Phylogenetic analyses confirmed that S. pimpinellifolium is the closest ancestor of all cultivated tomatoes. Local accessions all clustered together and were strictly related with other cultivated tomatoes (S. lycopersicum group). Noteworthy, S. lycopersicum var. cerasiforme resulted in a mixture of both cultivated and wild tomato genotypes since one of the two analyzed accessions clustered with cultivated tomato, whereas the other with S. pimpinellifolium. Overall, our results revealed a very reduced cytoplasmic variability in cultivated tomatoes and suggest the occurrence of a cytoplasmic bottleneck during their domestication.